2013
DOI: 10.1111/iep.12038
|View full text |Cite
|
Sign up to set email alerts
|

Implications of combined ovariectomy and glucocorticoid (dexamethasone) treatment on mineral, microarchitectural, biomechanical and matrix properties of rat bone

Abstract: Osteoporosis is one of the deleterious side effects of long-term glucocorticoid therapy. Since the condition is particularly aggressive in postmenopausal women who are on steroid therapy, in this study we have attempted to analyse the combined effect of glucocorticoid (dexamethasone) treatment and cessation of oestrogen on rat bone. The dual aim was to generate osteoporotic bone status in a short time scale and to characterise the combination of glucocorticoid-postmenopausal osteoporotic conditions. Sprague Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
9
22
1
2
Order By: Relevance
“…Being consistent with our findings, previous studies [32][33][34][35][36] demonstrated GCs were able to generate deterioration of bone microarchitecture, which but rarely compared the effect of different types of GCs on bone microarchitecture. In our study comparing the influence of DEXA and MP, lower BS/BV, CONN.D, Tb.N and higher Tb.Sp were observed in DEXA group compared with MP group, and there are less transverse trabecular number and significantly higher trabecular separation in DEXA group than MP group ( figure 4j, k), accordingly, we could conclude that DEXA induced more deteriorative spinal microarchitecture than MP, making the spine be susceptible to fragile fracture.…”
Section: Recommendations For the Prevention And Treatment Of Glucocorsupporting
confidence: 93%
See 2 more Smart Citations
“…Being consistent with our findings, previous studies [32][33][34][35][36] demonstrated GCs were able to generate deterioration of bone microarchitecture, which but rarely compared the effect of different types of GCs on bone microarchitecture. In our study comparing the influence of DEXA and MP, lower BS/BV, CONN.D, Tb.N and higher Tb.Sp were observed in DEXA group compared with MP group, and there are less transverse trabecular number and significantly higher trabecular separation in DEXA group than MP group ( figure 4j, k), accordingly, we could conclude that DEXA induced more deteriorative spinal microarchitecture than MP, making the spine be susceptible to fragile fracture.…”
Section: Recommendations For the Prevention And Treatment Of Glucocorsupporting
confidence: 93%
“…These results seem to conflict with some of previous studies which reported that MMP9, Sclerostin, Cathepsink were up-regulated [16,32,50]. However, in fact, this confliction may attribute to multiple factors such as different duration of GCs intervention and varied site of bone sample.…”
Section: Recommendations For the Prevention And Treatment Of Glucocorcontrasting
confidence: 76%
See 1 more Smart Citation
“…The first determinant depends on the availability of an animal model that mimics a human disease involving bone repair so that the data generated can be used to predict the drug efficacy and safety in patients. Examples of animal models with good predictability of clinical outcomes include models of postmenopausal osteoporosis [87][88][89][90][91][92], models of glucocorticoid induced bone loss [93][94][95][96], models of cancer metastasis to bone [97], disuse models [98,99], fracture healing models [100][101][102][103] and several others. The second determinant of successful experimentation relates to translational biomarkers of novel therapy efficacy and safety that can be accurately predicted and monitored in patients.…”
Section: Methods and Technologymentioning
confidence: 99%
“…Завдяки значному прогресу біології в останні роки існує мож-ливість аналізувати дію багатьох чинників, котрі впливають на метаболізм кісткової тканини, як in vivo, так і in vitro, що призвело до більш активного використання експери-ментального моделювання на тваринах [1][2][3][4][5][6]. Проте існуючі сучасні методи оцінки стану й метаболізму кісткової тканини є інвазивними (гістоморфометричне дослідження, визначен-ня біохімічних маркерів кісткового ремоде-лювання в сироватці крові тощо) і неінвазив-ними (комп'ютерна томографія, двофотонна рентгенівська денситометрія -ДРА), що може обмежувати оцінку результатів дослідження в динаміці експерименту [1,7,8].…”
Section: вступunclassified